The influence of psychological resilience and nursing practice environment on nurses' moral courage: A cross‐sectional study - Zhang Ruixin; He Shan; Tang Yongli; Jie Chen; Chen Qianzhu; Wang Xue (Wiley, 2024)
Abstract Aim To determine the relationship between psychological resilience, nursing practice environment, and moral courage of clinical nurses and also the factors influencing moral courage. Design Cross‐sectional study. Methods 586 nurses from a general hospital were selected by convenience sampling method in January 2023. The general information questionnaire, Nurses' Moral Courage Scale (NMCS), Resilience Scale, and Practice Environment Scale (PES) were measured. Hierarchical linear regression analysis was used to explore the influencing factors of clinical nurses' moral courage. Results Nurses' average moral courage score was 79.00 (69.00, 91.00). The nurses' moral courage was positively correlated with psychological resilience and nursing practice environment. Multivariate linear regression analysis showed that psychological resilience and nursing practice environment entered the regression equation, accounting for 23.4% of the total variation. Psychological resilience and nursing practice environment are the main factors affecting the moral courage of clinical nurses. Nursing managers should conduct moral courage training, develop a decent nursing practice environment, pay attention to the psychological emotions of nurses, and actively build a safe, open, and supportive atmosphere for moral behaviour.